GROWTH AND FITNESS FOR SCHOOLCHILDREN OF PUBLIC EDUCATION OF THE CITY OF PRESIDENTE FIGUEIREDO / AM (Fiep Bulletin - online, 2013)
The aim of the study was to describe the patterns of growth, body composition and physical fitness and health of children in the city of Presidente Figueiredo / AM, through a transversal approach using a battery of tests of motor performance and anthropometric measures. A sample of 894 subjects of both sexes aged from seven to 16 years, with 479 boys and 415 girls, duly enrolled in 2010 at the headquarters of the municipality of Presidente Figueiredo-AM. The results of anthropometric variables showed that girls are taller, heavier and had a higher accumulation of body fat than boys, and these indices considered similar to those that have been found in studies of national and international reference.Regarding the data of physical fitness tests related to health is observed that for flexibility girls showed higher levels of performance than boys. Regarding the variables of abdominal modified, the data indicate better performance of boys compared with girls. This information indicated that the boys probably move more than girls, featuring girls who show little motivation to practice regular physical activity.
Keywords: Growth; Body Composition; Physical Fitness.